Pharmacokinetics of sodium baicalin following intravenous and intramuscular administration to piglets. Issue 5 (2nd August 2019) - Liu, Yu; Zhao, Wenhua; Xu, Jianfeng; Yu, Xiaolin; Ye, Chun; Fu, Shulin; Qiu, Yinsheng
Abstract: The purpose of this study was to determine the pharmacokinetics of baicalin after intravenous and intramuscular administration of sodium baicalin at 50 mg/kg to piglets. Plasma baicalin levels were determined by high‐performance liquid chromatography. The plasma concentration–time data of baicalin for both administration routes were best described by two‐compartmental open model. The area under the plasma concentration–time curve and the elimination half‐lives were 77.47 ± 6.14 µg/ml × h and 1.73 ± 0.16 hr for intravenous and 64.85 ± 5.67 µg/ml × h and 2.42 ± 0.15 hr for intramuscular administration, respectively. The apparent volume of distribution and body clearance were 1.63 ± 0.23 L/kg and 2.74 ± 0.30 L h −1  kg −1 for intravenous and 0.51 ± 0.10 L/kg and 0.78 ± 0.08 L h −1  kg −1 for intramuscular routes, respectively. An intramuscular injection of sodium baicalin in piglets resulted in rapid and complete absorption, with a mean maximal plasma concentration of 77.28 ± 7.40 µg/ml at 0.17 hr and a high absolute bioavailability of 83.73 ± 5.53%.